Enhancing Maternal Knowledge to Prevent Stunting: A Systematic Review of Conventional and Video-Based Education Methods - Harni, Harni; Ahmad, Mardiana; Baso, Yusring Sanusi; Idrus, Hasta Handayani (Journal of Neonatal Surgery, 2025)
Background: Stunting remains a major public health problem with long-term consequences on child growth and development. Maternal education plays an important role in stunting prevention efforts. Various educational methods, including conventional approaches and video-based interventions, have improved maternal knowledge. Objective: To evaluate the effectiveness of conventional and video-based educational interventions in improving mothers' knowledge about stunting. Methods: A systematic review was conducted by searching relevant databases. A total of 15 eligible studies were included and analyzed based on study design, intervention type, population, knowledge assessment tools, and key findings. Methodological quality was assessed using the JBI Critical Appraisal Tool. Results: All studies reported an increase in maternal knowledge after the educational intervention. Video-based education showed more significant and consistent results compared to conventional methods. However, intervention design, media, and duration variations contributed to the heterogeneity of findings. Conclusion: Video-based education is an effective and promising approach to improve mothers' knowledge about stunting. Further research using a robust experimental design and long-term evaluation is recommended to assess its impact on behavior change in stunting prevention.